Congenital Deficiency of Alpha-2-Adrenoceptors on Human Platelets : Description of Two Cases - Tamponi, Giacomo; Pannocchia, Antonella; Arduino, Carlo; Bazzan, Mario; Dora, Nadine Della; Schinco, Piercarla; Buraglio, Mauro; Eandi, Mario (Thrombosis and Haemostasis, 1987)
The biochemistry and functionality of platelets from two related subjects (mother and son) with alpha-2-adrenoceptor-deficient platelets has been evaluated. Radioligand binding experimentes with the specific alpha-2-adrenergic-receptor antagonist, 3H-yohimbine, showed a drastic reduction of alpha-2-adrenoceptors in platelets from both subjects in comparison with the control values. Electron microscopy studies revealed a normal morphology and a normal number of alpha granules and dense bodies. Levels of adenine nucleotides; 5-hydroxytryptamine; B-thromboglobulin; platelet-factor-4 and thromboxane A2 production were within normal limits.Platelet aggregation and 5-hydroxytryplamine production in response to adrenalin (at concentrations up to 50 μM) were absent, whereas ADP, AA, PAF, collagen and thrombin-induced aggregation, secretion, Ca++ flux and thromboxane A2 production were normal.The inhibitory effect caused by different concentrations of prostacyclin on Ca++ flux, aggregation, secretion and thromboxane A2 production of platelet functionally lacking of alpha-2-adrenoceptor was not distinguishable from control platelets and platelets preincubated with yohimbine.
Keywords: Alpha-2-adrenoceptors; Human platelets; Congenital deficiency